2001
DOI: 10.1177/0146167201277002
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity of Interpersonal Circumplex Traits

Abstract: The existence of interpersonal complementarity at a stylistic level using the Interpersonal Adjectives Scales (IAS) and the optimal definition of complementarity were the foci of the study. The IAS ratings made by three samples of college students were used: 265 rated both of their parents, 346 rated themselves and their closest friend, and 136 rated how they expected themselves and the other participant to behave in one of three very different situations. The correlation matrices between the scores of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 51 publications
(133 reference statements)
2
76
1
Order By: Relevance
“…1). Past research has demonstrated that the IAS-R conforms to the structure of the IPC (Tracey & Schneider, 1995;Tracey, Ryan, & Jaschik-Herman, 2001;Wiggins, 1995). In the current sample, the mean internal consistency estimate of the eight scales was .85.…”
Section: Interpersonal Stylementioning
confidence: 50%
“…1). Past research has demonstrated that the IAS-R conforms to the structure of the IPC (Tracey & Schneider, 1995;Tracey, Ryan, & Jaschik-Herman, 2001;Wiggins, 1995). In the current sample, the mean internal consistency estimate of the eight scales was .85.…”
Section: Interpersonal Stylementioning
confidence: 50%
“…As seen in Table 1, all of the randomization tests examining the circular structure of the informant IAS-R octant scales were significant, and none of the random matrices fit the circular structure of the IPC better than the original correlation matrices. Women's reports of their roommates' interpersonal styles fit the circular structure slightly better than the male reports of their roommates' interpersonal styles (CI difference = .06, p < .05; Tracey, 1994;Tracey et al, 2001). However, the high CIs in Table 1 indicate that both men's and women's reports of their roommates interpersonal styles strongly conformed to the circular structure presented in Figure 1.…”
Section: Number Of Correct Predictions -Number Of Incorrect Predictiomentioning
confidence: 82%
“…Research has found the presence of complementarity at the more global, stylistic trait level in relatively longer term relationships (Tracey et al, 2001). Further research has also determined that, in naturalistic settings, complementarity of observed behavior between dyad partners increases over time and these changes are reflected in informant ratings but not in self-ratings (Markey & Kurtz, 2006).…”
Section: Ansell Et Al / Gender Differences In Complementarity 503mentioning
confidence: 99%
“…The dynamics of interpersonal behavior have been analyzed in physician-patient interactions (e.g., Tracey 2004), parent-child interactions (e.g., Markey et al 2005), peers', friends', and partners' interactions (e.g., Tracey et al 2001), but not in the context of coaching. Interpersonal affiliation and dominance have been analyzed on the basis of trait ratings as well as on the basis of interaction behavior, and have been used to describe situational dynamics in which interacting partners exert mutual influence (cf.…”
Section: The Role Of Interpersonal Behavior In Coaching Interaction Pmentioning
confidence: 99%